PENGARUH PERHATIAN ORANGTUA TERHADAP PRESTASI BELAJAR DI SMPN 3 SIMPENAN TAHUN 2019 - Nawawi Nawawi (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2021)
student achievement (2) to determine the effect of parent attention on student achievement. Quantitative approach. Correlation method by explaining the relationship of variable X with variable Y, in this case correlation by explaining the relationship and the effect of parent attention on student achievement. The results of the study (1) there is a significant functional relationship between the variables of parent attention to student learning achievement. F count of tuna matches 1,154 <f table 2.42 meaning that the relationship of parent attention to learning achievement is linear, or the regression of Y over X is linear. (2) The magnitude of the effect of variable X on variable Y = 11.8%, the relationship of parent attention to student achievement = 0.343, the remaining 88.92% was determined by other factors. Keywords: Parent attention, Student learning, achievement